Undesired Oscillations in Pneumatic Systems - João Falcão Carneiro (2011)
Abstract: Automatic positioning devices are worldwide used in tasks like handling or assembly, making them key components of modern manufacturing systems. Pneumatic solutions are usually less expensive than their electrical counterparts, are more reliable and require less maintenance. However, the complex nonlinear nature and high model order of pneumatic systems lead to a very difficult control task. This paper illustrates these difficulties by presenting a study where several linear controllers are experimentally tested. In fact, despite their simplicity, these controllers can lead to undesired oscillations in the system output. The causes of these oscillations are described and justified in detail.